ANALISIS PERKARA PENOLAKAN IZIN POLIGAMI DI PENGADILAN AGAMA MUNGKID ( Terhadap Putusan Hakim Nomor : 1469/Pdt.G/2023/PA.Mkd ) - Buana , Gita Arum; Jalil, Abdul; Fitriyah, Siti Magfirotul (IQTISODINA, 2025)
This study aims to analyze the legal considerations behind the rejection of a polygamy request by the Mungkid Religious Court, based on Decision No. 1469/Pdt.G/2023/PA.Mkd. Although the applicant fulfilled several formal requirements, including the first wife’s consent, the request was denied because its primary motive was to legalize the status of a child from an extramarital relationship. The research uses a normative juridical method with a descriptive-analytical approach to the court’s decision. The analysis reveals that the request was considered unlawful as it failed to meet the legitimate religious and legal grounds defined in the Marriage Law and the Compilation of Islamic Law (KHI). The judge concluded that polygamy must be based on substantial reasons, such as the wife’s inability to fulfill marital duties, serious illness, or infertility. This case highlights that spousal consent alone is insufficient without valid legal justification and evidence of the husband's financial and social capacity. Therefore, the court plays a crucial role in ensuring justice and protecting the rights of women and children.